Exploring English Teaching Materials for candidate Nurse (A Need Analysis at Nursing Department Poltekkes Kemenkes Semarang) - Purianingtyas, Allen Rufaida; Nofianto, Norma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
English for Nursing is closely related to English for Specific Purpose (ESP) since its purpose and function is in accordance with the needs of English in nursing circumstances. It is necessary to identify the students and lecturers needs in some categorization such as the target situation and objective needs analysis, linguistic, discourse and genre analysis, subjective Needs Analysis, present Situation Analysis, and means analysis. The participants are the 90 students of Nursing Department in Diploma Three Program that were and the lecturers of nursing department. The elaboration involved the capability in listening, speaking, reading and writing. The other aspects also strongly concerned to improve such as vocabulary, nursing terminology, and English grammar. The learning process that plays important roles in learning outcomes that all of the materials must be in accordance with the students’ performance as professional nursing.